Simultaneous Graph Drawing: Layout Algorithms and Visualization Schemes - Erten, Cesim; Kobourov, Stephen; Le, Vu; Navabi, Armand (Journal of Graph Algorithms and Applications, 2005)
In this paper we consider the problem of drawing and displaying aseries of related graphs, i.e., graphs that share all, or parts of thesame node set. We present three algorithms for simultaneous graphdrawing and three visualization schemes. The algorithms are based on amodification of the force-directed algorithm that allows us to takeinto account node weights and edge weights in order to achieve mentalmap preservation while obtaining individually readable drawings. Thealgorithms and visualization schemes have been implemented and thesystem can be downloaded athttp://simg.cs.arizona.edu/. <!---->